2008
DOI: 10.1007/s10811-008-9395-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acadian marine plant extract powder from Ascophyllum nodosum in tissue culture of Kappaphycus varieties

Abstract: Three varieties of Kappaphycus alvarezii (Kapilaran, KAP), Tambalang purple (PUR), Adik-adik (AA), and one variety of Kappaphycus striatum var. sacol (green sacol (GS) were used to determine the efficiency of Acadian marine plant extract powder (AMPEP) as a culture medium at different concentrations, for the regeneration of young plants of Kappaphycus varieties, using tissue culture techniques for the production of seed stock for nursery and outplanting purposes for the commercial cultivation of carrageenophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 23 publications
(31 reference statements)
1
36
0
2
Order By: Relevance
“…Successful culture of micropropagules of K. alvarezii was already done in the laboratory (Dawes and Koch 1991;Dawes et al 1993Dawes et al , 1994. Smaller sections of seaweeds were used for tissue culture and showed some promise (Muñoz et al, 2006;Hurtado and Biter 2007;Hurtado et al 2009;Hayashi et al 2008). Tetrasporophyte progenies have been shed in the laboratory and grown outdoors (Bulboa et al 2007(Bulboa et al , 2008Bulboa and De Paula 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Successful culture of micropropagules of K. alvarezii was already done in the laboratory (Dawes and Koch 1991;Dawes et al 1993Dawes et al , 1994. Smaller sections of seaweeds were used for tissue culture and showed some promise (Muñoz et al, 2006;Hurtado and Biter 2007;Hurtado et al 2009;Hayashi et al 2008). Tetrasporophyte progenies have been shed in the laboratory and grown outdoors (Bulboa et al 2007(Bulboa et al , 2008Bulboa and De Paula 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The collection sites have grown the explants commercially recently along the coast of the Zamboanga Peninsula. The plants were placed in an ice chest lined with seawater-moistened cheesecloth and transported to the Aquaculture Department of the Southeast Asian Fisheries Development Center (SEAFDEC/AQD) Tigbauan, Iloilo, Philippines, following the protocol described by Hurtado et al (2009). The explants were acclimatized in concrete tanks with continuous aeration and a flow-through seawater system for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The application of AMPEP has been extended to laboratory tissue culture techniques for the regeneration of the carrageenophyte Kappaphycus alvarezii varieties for nursery purposes in the Philippines (Hurtado et al 2009). Loureiro et al (2009) also reported on a substantial increase in the growth rates of K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acadian marine plant extract powder (AMPEP) is another alga powder that can improve callus growth. This alga powder is obtained from fresh Ascophyllum nodosum and contains the major and minor nutrients, carbohydrates, amino acids and plant growth promoting substances which are required for callus growth 39 .…”
Section: −1mentioning
confidence: 99%